DIGITAL COMMUNICATION STRATEGY OF SAMPUL BELAKANG GORONTALO FOR LITERACY AND CULTURAL CONTENT DISTRIBUTION ON INSTAGRAM - Fitrah Yusharyani Puluhulawa; Citra Fransisca Indah Lestari Dano Putri; Muhammad Akram Mursalim (Jurnal Ilmiah Publipreneur, 2026)
Digital communication has become central to how grassroots literacy communities build visibility, organize participation, and distribute cultural meanings. This study aims to analyze the digital communication strategy of Sampul Belakang Gorontalo in distributing literacy and cultural content through Instagram. Using qualitative content analysis, the study examined 63 Instagram feed posts uploaded from January to May 2026 as multimodal communication units consisting of visuals, captions, hashtags, collaborator tags, calls to action, and visible audience responses. The findings show that the account constructs Instagram as a community-based infrastructure rather than a mere announcement channel. Poetry and radio broadcasting through Selamat Malam Puisi emerged as the dominant category, indicating the centrality of affective literacy and emotional audience relations. However, posts on critical discussion, organizational regeneration, and community participation generated stronger visible responses, showing that engagement is shaped by issue relevance, member identity, and participatory orientation. The visual strategy relies mainly on poster-based announcements and carousel documentation, while the message strategy combines affective-poetic, critical-argumentative, informative-organizational, documentary-appreciative, and participatory communication. This study contributes to digital communication and literacy studies by introducing community-based literacy-cultural distribution as a framework for understanding how local communities produce public knowledge, cultural memory, and collective identity through Instagram. Keyword: Digital communication strategy; Instagram; literacy community; cultural content distribution; Sampul Belakang Gorontalo